Response and recovery from Covid-19 in historic urban destinations (cases from Belgium and the Netherlands) - Dominique Vanneste; Vere Van Meeteren; Bart Neuts (Via@)
Covid-19 affected tourism in a particularly hard way, forcing stakeholders at all levels to work on recovery while a number of experts pointed out that the pandemic constituted a momentum to change the future face of tourism. This paper focusses on a potential implementation gap, researching the question how local stakeholders handle the Covid-19 pandemic in practice, both in the short run and in longer term recovery strategies. Is a “business as usual” approach prevalent or can the pandemic be a catalyst for (major) transformations? The cases researched are historic cities in Belgium and the Netherlands. Although these countries lack a dominant tourism industry, especially their cities, as destinations, suffered considerably. Short-term crisis management as well as the vision, strategy and actions on how to recover in the long term, were the subject of a number of online workshops with tourism planning and management officials. These online workshops used an interesting software (MURAL) to fuel the interactive exchange of information and discussion.